Evaluating the Link Between Cardiovascular Risk and Alzheimer’s Disease: A Comprehensive Case-Control Study in Castilla y León, Spain - Laura Bello-Corral; Jesús Seco-Calvo; Marta Celorrio San Miguel; Evelina Garrosa; Diego Fernández-Lázaro; Leticia Sánchez-Valdeón (Applied Sciences)
Alzheimer’s disease (AD) represents a growing public health challenge due to its increasing prevalence, projected to reach 150 million cases by 2050. Characterised by neuropathological changes such as the accumulation of beta-amyloid peptide and hyperphosphorylated Tau protein, the disease is related to genetic and environmental factors. The main objective of this research has been to analyse the possible relationship between some cardiovascular factors and AD. This analytical observational case-control study carried out in Castilla y León (Spain), comprised a total of 511 individuals between 60 and 90 years of age, of whom 260 had a diagnosis of AD and the rest were healthy individuals. The results showed that the group with AD were predominantly women, widowed and with primary education, who showed a higher prevalence of family history of the disease. It was also observed that hypertension, cardiac pathology and diabetes mellitus were three cardiovascular risk factors that showed significant increased differences in the group of AD patients compared to the group of control individuals. Although the precise mechanisms require further research, these results underline the importance of addressing complex interactions between genetic and environmental factors in the prevention of AD.